Differences in performance and injury profile in soccer players: A comparison across age-categories and positions - Torres-Martín, L.; Sánchez-Sánchez, J.; Ramirez-Campillo, R.; Raya-González, J. (Kinesiology, 2025)
The aims of this study were to compare physical performance and injury profiles across different age categories and playing positions of soccer players, and to establish relationships between physical performance tests and positions. Soccer players of different age categories, senior (n=34), under-19 years (U19; n=53) and under-16 years (U16; n=54), performed countermovement jump (CMJ), change of direction (COD, 10+10-m with 90° turn), and linear sprint over 30-m tests. Change-of-direction loss was calculated. Injuries (i.e., incidence and burden) during the first phase of the season were recorded. Senior players showed the best performance in COD (effect size [ES] = 1.23-1.42), the U19 players were the best in sprint over 30-m (ES = 0.64-1.44) and the worst in COD loss (ES = 1.18-1.68). The U16 players showed the lowest values in countermovement jump (ES = 0.90-1.00) and linear sprint tests (ES = 0.64-1.46). No differences in physical performance were reported for the playing positions analysis. Senior players showed the highest total injury incidence and the greatest burden values, while wide midfield players presented the highest burden values. These results indicate that individualized training programs must be applied based on age and playing positions.